Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1039/d1me00118c
|View full text |Cite
|
Sign up to set email alerts
|

Rationally designed foldameric adjuvants enhance antibiotic efficacy via promoting membrane hyperpolarization

Abstract: Antimicrobial foldamers reduce the antibiotic resistance in multi-drug resistant Gram-negative bacteria. They hyperpolarize the membrane at low concentrations by acting as selective ionophores, enhancing the GHK-potential across the membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…We observed that charged Lys side chains are in close contact with the phosphate moieties of the membrane even at high tilt angles, snorkeling up from the peptide backbone to the charged lipid layer. The Lys side chain length limits the peptide tilt depth , until interaction with mobile ions, and desolvation enables further insertion of the helix and cross-membrane ion transport . Tilted peptide populations were obtained in previous studies by a synergistic interaction with magainin 2 , or other PGLa peptides with increased P / L ratio .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We observed that charged Lys side chains are in close contact with the phosphate moieties of the membrane even at high tilt angles, snorkeling up from the peptide backbone to the charged lipid layer. The Lys side chain length limits the peptide tilt depth , until interaction with mobile ions, and desolvation enables further insertion of the helix and cross-membrane ion transport . Tilted peptide populations were obtained in previous studies by a synergistic interaction with magainin 2 , or other PGLa peptides with increased P / L ratio .…”
Section: Resultsmentioning
confidence: 99%
“…It is a 21-amino-acid peptide with a net charge of +5 that folds into a helix on the membrane surface. Besides its direct antibiotic effect, PGLa acts as an adjuvant administered in combination with small molecule antibiotics . These experiments concluded that the peptide insertion into the membrane induced hyperpolarization, and the elevated transmembrane potential (TMP) was confirmed in vesicular model systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with our findings, promoting membrane hyperpolarization has been reported as an adjuvant strategy to enhance antibiotic efficacy. 55 The schematic diagram describing the idea of the adjuvant strategy based on AuNCs is presented the Fig. 9.…”
Section: Killing By the Combination Of Aunc@cpp And Antibiotics Is Du...mentioning
confidence: 99%
“…Moreover, Hills also defined a foldamer as "any oligomer that folds into a conformationally ordered state in solution" [3]. Foldamers have been broadly used in organocatalysis [4,5], materials chemistry [6], polymer chemistry [7], chemical biology [8,9], and medicinal chemistry [10,11] because of their unique structural properties and adaptabilities [12,13]. In particular, it has been clearly demonstrated that foldamers mimic biomacromolecules and are resistant to degradation by digestive enzymes [13].…”
Section: Introductionmentioning
confidence: 99%